Early life determinants of arterial stiffness in neonates, infants, children and adolescents: A systematic review and meta-analysis. (August 2022) - Varley, Benjamin J.; Nasir, Reeja F.; Craig, Maria E.; Gow, Megan L.
Abstract: Background and aims: Certain exposures and risk factors during the first 1, 000 days of life are known to influence future cardiovascular disease (CVD) risk. Pulse wave velocity (PWV) is a measure of arterial stiffness and a recognised surrogate marker of CVD. We performed a systematic review and meta-analyses to investigate whether early life exposures were associated with increased PWV compared with controls in youth. Methods: Databases AMED, MEDLINE, EMBASE, CINAHL and Scopus were searched from inception until February 2022. Eligibility criteria: observational controlled studies in youth aged <20 years with risk factors/exposure during the first 1, 000 days and PWV measurement. This review is registered with PROSPERO (CRD42019137559). Outcome data were pooled using random-effects meta-analysis. Meta-regression was used to investigate potential confounders. Results: We identified 24 eligible studies. Age of participants ranged from 1-day to 19-years at time of PWV assessment. Exposures included pre-term birth, small for gestational age (SGA), maternal diabetes and assisted reproductive technologies, none of which were significantly associated with PWV in meta-analysis. Sub-group analysis by age demonstrated increased PWV in childhood and adolescence in those exposed to maternal diabetes or born SGA. In meta-regression of pre-term studies, higher prevalence of SGA was associated with increased PWV compared with controls ( p  = 0.034, R 2  = 1). Conclusions: We found limited evidence that youth exposed to maternal diabetes or born SGA have increased PWV, consistent with increased future CVD risk. These changes in PWV appear to manifest in later childhood and adolescence. Further research is required to better understand the observed relationships. Graphical abstract: Image 1 Highlights: This is the first review to investigate pulse wave velocity in youth and exposure to early life risks. Limited evidence supports increased pulse wave velocity when exposed to maternal diabetes or born small for gestational age. These changes in pulse wave velocity appear to manifest in childhood and adolescence. Further research is required to better understand the observed associations.